Biocompatibility and in vivo operation of implantable mesoporous PVDF-based nanogenerators. (September 2016) - Yu, Yanhao; Sun, Haiyan; Orbay, Hakan; Chen, Feng; England, Christopher G.; Cai, Weibo; Wang, Xudong
Abstract: The rapid developments of implantable biomedical electronics give rise to the motivation of exploring efficient and durable self-powered charging system. In this paper, we report a mesoporous polyvinylidene fluoride (PVDF)-based implantable piezoelectric nanogenerator (NG) for in vivo biomechanical energy harvesting. The NG was built with a sponge-like mesoporous PVDF film and encapsulated by polydimethylsiloxane (PDMS). After embedding this NG into rodents, a V oc of 200 mV was produced from the gentle movement of rodent muscle. Meanwhile, no toxicity or incompatibility sign was found in the host after carrying the packaged NG for 6 weeks. Moreover, the electric output of this NG was extremely stable and exhibited no deterioration after 5 days of in vivo operation or 1.512×10 8 times mechanical deformation. This NG device could practically output a constant voltage of 52 mV via a 1 μF capacitor under living circumstance. The outstanding efficiency, magnificent durability and exceptional biocompatibility promise this mesoporous PVDF-based NG in accomplishing self-powered bioelectronics with potentially lifespan operation period. Graphical abstract: Highlights: Photographs of implanted PVDF nanogenerator inside a living mouse. In vivo voltage output of the packaged PVDF nanogenerator within 5 days operation.